Systematic review of histological remission criteria in eosinophilic esophagitis. Issue 4 (13th June 2018) - Eke, Ransome; Li, Tong; White, Anna; Tariq, Tooba; Markowitz, Jonathan; Lenov, Andrey
Abstract : Elemental diets, dietary elimination, and steroid therapies are the most common therapies in the clinical trials for eosinophilic esophagitis (EoE). Histological findings (usually reported as eosinophils per microscopic high‐powered field [hpf]) remain the most common end‐point used to define response. Yet, the threshold for defining "response" and "remission" are ill‐defined among consensus guidelines and may vary from study to study. We conducted a systematic literature review of articles on eosinophilic esophagitis, published between January 2007 and November 2017, considering histological remission as the primary outcome. We abstracted treatment information and definitions of histological remission or response. A comparison of definitions of histological remission across and within institutions was performed. A total of 61 articles were included in this review, with approximately 60% of the studies published from centers in the United States. Histological definitions of remission of EoE ranged from 0 to ≤20 eosinophils/hpf. The most stringent criteria, ranging from 0 to ≤5 eosinophils/hpf, were commonly used in interventional trial studies that examined the effects of new treatments. We found remarkable variability in definitions between studies, treatment types, and regions. Age or epidemiological distribution of study subjects did not influence the criteria for histological remission. Clinical and histological improvements are important measures of the effects of treatment. Histological findings, the most objective measure of treatment, should provide an optimal method for comparing the effectiveness of various treatments. Yet, our findings suggest a lack of consistent remission criteria in published studies. Considering these inconsistencies, it is difficult to compare the effectiveness of various treatments. Abstract : Elemental diets, dietary elimination, and steroid therapies are the most common therapies in clinical trials for eosinophilic esophagitis (EoE). The threshold for defining "response" and "remission" are ill‐defined among consensus guidelines and may vary from study to study. This systematic review suggest a lack of consistent remission criteria in published trials and therefore difficult to compare effectiveness of various treatment formulas.